Employees acceptance of human resource information system (Bio D’scan Fingerprint Time Attendance): an exploratory study in Sarawak Economic Development Corporation / Zulfadli Abdul Rahman - Abdul Rahman, Zulfadli (2013)
The Sarawak Economic Development Corporation (SEDC) was established on 1st March 1972 as a state owned statutory body with the general aim of promoting the commercial, industrial and socio-economic development of the State. SEDC was established under the Perbadanan Pembangunan Ekonomi Sarawak Ordinance (Sarawak Cap. 35), a law duly passed by the Sarawak State Assembly in accordance with the powers conferred on and delegated to the State Government of Sarawak under the Constitution of Malaysia. While SEDC is a statutory body establised under the laws of the State of Sarawak, is also comes under the purview of the Federal Government of Malaysia through the Federal Ministry of Finance (MOF).